Laboratory statistics handbook of formulas and terms - Kallner, Anders (Elsevier, 2014)
Laboratory Statistics: Handbook of Formulas and Terms presents common strategies for comparing and evaluating numerical laboratory data. In particular, the text deals with the type of data and problems that laboratory scientists and students in analytical chemistry, clinical chemistry, epidemiology, and clinical research face on a daily basis. This book takes the mystery out of statistics and provides simple, hands-on instructions in the format of everyday formulas. As far as possible, spreadsheet shortcuts and functions are included, along with many simple worked examples. This book is a must-have guide to applied statistics in the lab that will result in improved experimental design and analysis. Comprehensive coverage of simple statistical concepts familiarizes the reader with formatted statistical expressionSimple, worked examples make formulas easy to use in real lifeSpreadsheet functions demonstrate how to find immediate solutions to common problemsIn-depth indexing and frequent use of synonyms facilitate the quick location of appropriate procedures.